Gastrointestinal helminths of small mammals (Rodentia and Carnivora) in the vicinity of Usholta, Georgia - Ketevan Nikolaishvili; Tsitsino Lomidze; Lela Arabuli; Ketevan Asatiani; Lali Murvanidze (Caucasiana)
In this study, we investigated the gastrointestinal helminth fauna of small mammals in the highland region of Usholta (Racha, Western Georgia). In total, 19 specimens of small mammals were examined, of which 10 gastrointestinal helminth species were detected. Five out of eight specimens of Apodemus uralensis were infected with three nematode species: Heligmosomoides polygyrus, Syphacia obvelata, and Trichuris muris. Notably, the liver of a single individual of A. uralensis was also infected with cestode—Echinococcus multilocularis, (larvocysts) —a novel host record for this parasite in Georgia. All eight exeminated Microtus daghestanicus specimens were infected with both cestode (Paranoplocephala omphalodes and Rodentolepis asymmetrica) and nematode (Heligmosomum costellatum and Syphacia sp.) parasites. Similarly, all three exeminied specimens of Mustela nivalis were infected with cestodes (Versteria mustelae) and nematodes (Molineus patens, Syphacia sp.). For Syphacia sp., M. nivalis is a new host record in Georgia. Only one specimen of A. uralensis was simultaneously infected by two species of nematodes (Syphacia sp., T. muris) and also a single individual of M. nivalis was infected with three species of helminths (V. mustelae, M. patens, Syphacia sp.). This study provides valuable insights into the helminth diversity and host-parasite relationships in the region, highlighting the importance of continued research on wildlife parasites.